SASTRA DAN WACANA SEKSUALITAS: Sebuah Dominasi Maskulinitas Perempuan di Indonesia - M Yasin (Universitas Islam Negeri (UIN) Mataram, 2016)
This study aims to determine the discourse of sexuality displayed in the form of literature in a collection of poems Shinta Febrianty, Aku bukan Masa Depan and a novel Tujuh Tahun Semusim by Clara Ng. This study is multidisciplinary study based on cultural studies by combining a number of perspectives including grammatology theory and discourse deconstruction from Jacques Derrida and power relations theories from Michel Foucault. The study used Critical Discourse Analysis (CDA) as analysis method. The result showed that “sex scenes” displayed both authors in their work have become a discourse not only in the realm of literature, but in the context of the wider society. Through the discourse of sexuality, it is revealed that the practice of power relations with the strengthening of the institutional discourse of religious morality regime by the previous regime, which helped contesting in the ideological struggle of power in Indonesia. The ideology of previous rulers which had been the benchmark of dominant discourse produces a variety of products in managing sexuality in society.